The road to pandemic recovery: Tracking COVID-19's impact on cirrhosis care and outcomes among 111,558 Veterans - Adejumo, Adeyinka C.; Yakovchenko, Vera; Morgan, Timothy R.; Spoutz, Patrick; Chia, Linda; Bajaj, Jasmohan S.; Chang, Michael F.; Dominitz, Jason A.; Rogal, Shari S. (Hepatology (Baltimore, Md.), 2023)
Background & Aims: This study aimed to evaluate quarterly trends in process and health outcomes among Veterans with cirrhosis and assess the factors associated with cirrhosis outcomes before and during the COVID-19 pandemic. Approach & Results: US Veterans with cirrhosis were identified using the Veterans Health Administration Corporate Data Warehouse. Quarterly measures were evaluated from September 30, 2018, through March 31, 2022, including twice yearly screening for hepatocellular carcinoma (HCC-6), new HCC, surveillance for or treatment of esophageal varices, variceal bleeding, all-cause hospitalization, and mortality. Joinpoint analyses were used to assess the changes in trends over time. Logistic regression models were used to identify the demographic and medical factors associated with each outcome over time. Among 111,558 Veterans with cirrhosis with a mean Model for End-stage Liver Disease-Sodium of 11±5, rates of HCC-6 sharply declined from a prepandemic peak of 41%, to a nadir of 28%, and rebounded to 36% by March 2022. All-cause mortality did not significantly change over the pandemic, but new HCC diagnosis, EVST, variceal bleeding, and all-cause hospitalization significantly declined over follow-up. Quarterly HCC diagnosis declined from 0.49% to 0.38%, EVST from 50% to 41%, variceal bleeding from 0.15% to 0.11%, and hospitalization from 9% to 5%. Rurality became newly, significantly associated with nonscreening over the pandemic (aOR for HCC−6=0.80, 95% CI 0.74 to 0.86; aOR for EVST=0.95, 95% CI 0.90 to 0.997). Conclusions: The pandemic continues to impact cirrhosis care. Identifying populations at the highest risk of care disruptions may help to address ongoing areas of need.